Research and analysis of modernization processes in food industry enterprises of Ukraine - Buzhimska K.O.; Stankevich N.A. (Проблеми теорії та методології бухгалтерського обліку, контролю і аналізу)
The modernization of domestic enterprises is a prerequisite for the integration of Ukraine into the European Union, first of all it concerns food industry enterprises, because they have the greatest potential for access to European markets with their own products. Accelerated modernization will provide an opportunity to improve the quality and safety of domestic food products and bring them closer to world standards. The methods and methodology of economic and statistical analysis remain the focus of the scholars. The analysis of trends, directions of development, and results of activities creates a basis for the adoption of quality management decisions, both at the strategic and operational levels. The study of the modernization process is impossible without the use of methods of economic and statistical analysis for a general evaluation of its state and efficiency. The paper proposes the relative indicators of asset value dynamics, residual value of fixed assets, volumes of sales, financial results before taxation, net profit for a generalizing assessment of the modernization process. It is substantiated that the modernization process is effective if the growth rate of asset value is greater than one unit, the growth rate of the residual value of fixed assets increases the growth rate of assets, the growth rate of sales of products is greater than the growth rate of residual value of fixed assets, the rate of growth of financial results before taxation is higher than the pace, the growth of sales volume, the growth rate of net profit is higher than the growth rate of the financial result before taxation. Using the Spirmeno coefficient, the authors obtained following results: the modernization process was most effective in 2011–2012, the modernization processes in food industry sharply slowed down during 2013–2015, but due to the already formed potential, they continue confirming the integral indices of the state and efficiency of modernization in 2014–2015. Further research is related to the research and analysis of modernization processes at the level of individual enterprises in order to expend successful experience and prevent negative outcomes.